Lithium-Ion battery solid electrolytes based on poly(vinylidene fluoride)-metal thiocyanate ionic liquid blends - Serra, João Pedro Cruz (2022)
Solid polymer electrolytes (SPEs) are required to improve battery safety through the elimination of the liquid electrolyte solution in current batteries. This work reports on the development of an SPE based on poly(vinylidene fluoride), PVDF, with the magnetic ionic liquid (MIL)1-butyl-3-methylimidazolium cobalt(II) isothiocyanate, [BMIM]2[(SCN)4Co], and its battery cycling behavior at room temperature. The addition of MIL in filler contents up to 40wt.%, to the PVDF polymer matrix does not affect the compact morphology of the samples obtained by solvent casting. The polar β-phase of PVDF increases with increasing MIL content, whereas the degree of crystallinity, thermal degradation temperature and mechanical properties of the MIL/PVDF blends decrease with increasing MIL content. The ionic conductivity of the MIL/PVDF blends increases both with temperature and MIL content, showing a highest ionic conductivity of 7 × 10-4 mS.cm-1 at room temperature for the MIL/PVDF blend with 40wt. % of MIL. The cathodic half-cells prepared with this blend as SPE show good reversibility and excellent cycling behavior at different C-rates, with a discharge capacity of 80 mAh.g-1 at C/10- rate with 99% of coulombic efficiency. The developed magnetic SPE is suitable for the next generation of sustainable lithium-ion batteries with excellent performance at room temperature, which performance can be further tuned by an external magnetic field.